Efficacy and safety of a facial serum containing snail secretion filtrate, Calendula officinalis, and Glycyrrhiza glaba root extract in the treatment of maskne: A randomized placebo‐controlled study. (27th July 2022) - Puaratanaarunkon, Thanaporn; Washrawirul, Chanudda; Chuenboonngarm, Nunthanach; Noppakun, Nopadon; Asawanonda, Pravit; Kumtornrut, Chanat
Abstract: Introduction: During the ongoing COVID‐19 outbreak, face mask use has increased and became a part of our daily lives. While wearing, prolonged contact time and microenvironmental change profoundly lead to an acne flare‐up, defined as "maskne." Aims: We aimed to assess the efficacy and safety of snail secretion filtrate, Calendula officinalis, and Glycyrrhiza glaba root extract combination serum (SCGS) in treating the maskne. Methods: This was a randomized, double‐blind, placebo‐controlled trial study. This study enrolled 66 participants with mild‐to‐moderate maskne. The SCGS and placebo were randomly assigned for participants to use twice daily for 12 weeks. Percentage change of acne lesion count, acne severity by Investigator Global Evaluation Acne (IGEA), sebum levels, corneometry levels, transepidermal water loss (TEWL), erythema score by Visia®, and adverse events were evaluated 4‐weekly at baseline to Week 12. At Week 12, all participants evaluated their satisfaction scores using a 10‐point visual analog scale (VAS). Results: In the mask‐covered area, the percent reduction in inflammatory acne lesions from the treatment group was significantly greater than the placebo group at all time points (coefficient of percentage change of inflammatory lesions = −33.89 [95% CI −65.24, −2.53]; p = 0.03). Also, a subgroup analysis with participants using concurrent acne treatments revealed similar results (12 participants, coefficient = −50.30 [95% −88.65, −11.95]; p = 0.01). However, there were no significant differences in non‐inflammatory lesions, all skin biophysics, and VAS between groups. Adverse events were mild and occurred in a few cases in both groups. Conclusions: The SCGS could significantly improve inflammatory acne lesions and had a favorable tolerability profile, suggesting its role as an adjunctive treatment in maskne.